Pengaruh Media Sosial terhadap Kesehatan Mental Remaja - Aan Tajudin; Puan Kayla Ayu Qolbiyyah; Nazwa Astri Alasa; Sri Mulyeni (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The advancement of digital technology has led to the extensive adoption of social media by teenagers. Social media has become a means of communication, entertainment, and an easily accessible source of information, but its use also has various impacts on adolescent mental health. This study aims to examine the influence of social media on adolescent mental health through a literature review approach. The method used was a literature review, reviewing various scientific journals, books, and academic articles relevant to the topic of social media and adolescent mental health. The data obtained was analyzed descriptively and qualitatively to identify patterns of findings and trends in previous research. The findings of the research show that social media usage has both beneficial and detrimental effects on the mental health of adolescents. On the positive side, social media also can be means of self-expression, expanding social networks, and obtaining emotional support. However, excessive and uncontrolled social media use possesses the ability to create adverse effects, such as increased anxiety, stress, depression, low self-confidence, and impaired self-image due to social comparison. Furthermore, exposure to negative content, cyberbullying, and pressure to gain social approval also contribute to the decline in adolescent psychological well-being. The duration of use, the type of platform, and adolescents' ability to manage emotions and time also influence the level of perceived impact. Therefore, the active role of parents, educators, and the social environment is needed to provide guidance and digital literacy education so that teenagers can utilize social media sensibly. Through effective management, it is anticipated that social media can be used constructively while prioritizing adolescent mental health.